Interconnecting DC busses of solar/wind based power supply system - Lee, Chong Tat. (2011)
The rising awareness of the recent increase in Earth surface temperature prompts human beings to reduce the production of heat and carbon dioxide. Besides, the cost of running oil/gas-based power plants will increase due to increasing crude oil price, while renewable energy power plants will become cheaper to install over time as technology matures. One of the clean energy viable for research purposes is the solar power.